APLIKASI PERHITUNGAN STOK BARANG DI WASERDA KOPERASI UNIT DESA MINARASA BATUKARAS DENGAN MENGGUNAKAN METODE AVERAGE - Aneu Yulianeu (LPPM STMIK DCI, 2017)
Batukaras Minarasa cooperatives engaged in savings and credit services and Waserda. For membership Waserda itself is entirely automatic membership in cooperatives that are in KUD Batukaras Minarasa. On cooperatives where the authors analyze and research, inventory calculations in Waserda KUD Minarasa still done manually Seara, pricing and inventory can not be seen whether it is new or old inventory, so that goods have long beaten flat with a new price, and it is harmful to consumers, would also greatly complicate the manual sellers in making, checks payable, pegecekan goods, daily revenue, or loss of profits, inventory taking hefty take a long time, and others .. Therefore, for these problems menaggulangi recommended alternative is by way of computerization. Both in terms of input data and reports as required.Keyword : KUD, Average Method